POSSIBILITIES OF EXTENDING DIGITAL HUMANITIES INTO SEMANTIC WEB ENVIRONMENT: THE CASE STUDY OF CROATIAN MEDIEVAL MANUSCRIPTS AND INCUNABULA AND THEIR FRAGMENTS - TOMIĆ, MARIJANA; WILLER, MIRNA (Knygotyra, 2013)
The article deals with the research on and description of medieval manuscripts and incunabula and their fragments as part of the digital humanities project in the context of the Semantic Web. It first describes the case study of Croatian medieval manuscripts and incunabula proposed as a research project by the Department of Information Sciences, University of Zadar. The focus of the project was directed at the selection of data elements required for detailed description of the mentioned material and their standardization using ontologies developed by the old and rare book community’s disciplines such as bibliography, codicology, palaeography and typography. A brief introduction to the technological infrastructure of the Semantic Web and its standards follows, with a detailed description of methodology to publish a selected vocabulary in one of the metadata registry services. This section of the article concludes with the RDF graph for the partially reconstituted record of a fragment description as an example of publishing linked open data. As each of the mentioned disciplines uses its own value vocabularies or ontologies, it is suggested that mappings between their terms is designed using SKOS rules, rather than aiming at the use of one common vocabulary.
Keywords: digital humanities; medieval manuscripts; incunabula; fragments; Croatia; Semantic Web; linked open data